An Integrative Model of Academic Supervision and Instructional Leadership for Strengthening Teachers' Pedagogical Competence through Religious Values - Revi Safitri; Muhammad Anggung Manumanoso Prasetyo (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
This study aims to examine the effectiveness of academic supervision through the principal's instructional leadership in strengthening teachers' pedagogical competence based on religious values ​​at SMP Negeri 1 Lhoksukon. This study used a qualitative, descriptive approach. Data were collected through observations, interviews, and documentation with the principal and several teachers as research informants. The results indicate that academic supervision is implemented systematically through program planning, learning observations, providing feedback, and follow-up coaching. The principal's instructional leadership plays a crucial role in directing, fostering, and evaluating the learning process, resulting in teachers improving their skills in developing learning materials, selecting varied methods, managing the classroom, and evaluating student learning outcomes to schools. Collaborative and ongoing academic supervision also supports the strengthening of religious values ​​in the learning process. Academic supervision through the principal's instructional leadership has been shown to contribute to improving teachers' pedagogical competence, learning quality, and religious culture in schools.